Analysis of Operational Planning in Increasing the Number of Umrah Pilgrims at PT Asyesa Hasanah Tour & Travel West Sumatra Padang City - Kalsum, Mita; Nurani, Khadijah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
This study aims to determine the operational planning of PT Asyesa Hasanah Tour & Travel West Sumatra Padang City and to find out what are the inhibiting factors for the operational planning of PT Asyesa Hasanah Tour & Travel West Sumatra Padang City in increasing the interest of umrah pilgrims after the Covid-19 pandemic. This research was a descriptive qualitative research by choosing. The background of this research is the decrease in the number of umrah pilgrims departing with PT Asyesa Hasanah Tour & Travel West Sumatra Padang City both before and after the Covid-19 pandemic. The result of study showed quite good results by analyzing the planning management carried out by PT Asyesa Hasanah Tour & Travel SUMBAR, Padang City before and after the Covid-19 pandemic and knowing the inhibiting factors in carrying out its planning management. There are changes in marketing strategies, products, and services offered to attract umrah pilgrims.